Minimum Weight Design of Trusses Using Heuristic Rules - Pyrz, M. (Engineering Transactions, 1996)
The minimum weight design of truss structures, composed of elements chosen from catalogues of available profiles, is presented in the paper. A controlled enumeration method is supplied with a knowledge module, containing the problem-oriented information, and represented symbolically. Heuristic rules, proposed on the basis of static analysis of the structure, are used to eliminate all "non-promising" propositions without numerical checking for feasibility. This approach leads to a great reduction (with respect to the "standard" enumeration) in the number of variants that have to be verified to find the global optimum. The application of knowledge-based enumeration is illustrated by numerical examples of standard truss optimisation problems for one or several loading conditions.